2019
DOI: 10.3390/s19020305
|View full text |Cite
|
Sign up to set email alerts
|

Robotic System for Inspection by Contact of Bridge Beams Using UAVs

Abstract: This paper presents a robotic system using Unmanned Aerial Vehicles (UAVs) for bridge-inspection tasks that require physical contact between the aerial platform and the bridge surfaces, such as beam-deflection analysis or measuring crack depth with an ultrasonic sensor. The proposed system takes advantage of the aerodynamic ceiling effect that arises when the multirotor gets close to the bridge surface. Moreover, this paper describes how a UAV can be used as a sensor that is able to fly and touch the bridge to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 28 publications
1
47
0
Order By: Relevance
“…The operations of these autonomous aerial robots are ranging from the inspection and maintenance of industrial facilities [4][5] to the assessment of big structures in postdisaster situations [6], such as earthquakes or man-made extreme events. In [7] and [8] the authors evaluated the feasibility of carrying out bridge inspections using UAVs which establish a full contact condition with the bridge.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The operations of these autonomous aerial robots are ranging from the inspection and maintenance of industrial facilities [4][5] to the assessment of big structures in postdisaster situations [6], such as earthquakes or man-made extreme events. In [7] and [8] the authors evaluated the feasibility of carrying out bridge inspections using UAVs which establish a full contact condition with the bridge.…”
Section: Introductionmentioning
confidence: 99%
“…Although the use of aerial robots for bridge inspection is not widely extended, the interest in this technology is growing significantly in previous years [9]. For instance, in [10] UAVs have been used for carrying out visual inspection and in [8] the authors proposed the use of aerial vehicles, that are able to touch and even maintain the contact with the bridge, increasing the use of the aerial robots in different applications.…”
Section: Introductionmentioning
confidence: 99%
“…The application range of UAV (Unmanned Aerial Vehicles) is significantly growing year after year [1]. However, most previous studies have been only focused from the operation point of view or showing experimental applications of this new technology, such as aerial manipulation [2] or inspection of infrastructure [3]. Nevertheless, there are more aspects that must be considered in real applications to guarantee that this technology can be applied in security conditions and commercially exploited.…”
Section: Section I Introductionmentioning
confidence: 99%
“…Although in most of these applications the UAV accomplish perceptive tasks such as exploration, monitoring or surveillance among others, there are some of them that directly involve interaction between the UAV and the environment and which are mainly carried out by aerial manipulators [2][3] [4]. These are a new concept of UAV with an integrated robotic manipulator which are used in tasks as contact inspection and sensor installation in inspection and maintenance (I&M) of infrastructures or industrial plants [5] [6]. These I&M tasks usually require that the aerial platform flies very close to different obstacles, for instance, the AEROARMS [7] and HYFLIERS [8] project are focused on aerial manipulation for outdoors applications in I&M in oil and gas plants or the RESIST [9] project which is about the I&M of large civil infrastructures as bridges or tunnels using UAV.…”
Section: Introductionmentioning
confidence: 99%
“…These aerodynamic effects have been previously studied [11] [12][13] [14] and also by the authors. In [15] a general overview of these kinds of effects was presented and some of them were specifically studied for different applications like the ground effect in [16] or ceiling effect in [6] [17]. These previous studies have shown that it is usually necessary to model this aerodynamic behaviour to guarantee that the final application produces a results which are good enough even flying very close to obstacles.…”
mentioning
confidence: 99%